Pengembangan Pariwisata Berbasis Masyarakat di Pulau Pinus II Desa Tiwingan Baru Kabupaten Banjar - Wibowo, Chahyo Agung; Rahmini, Noor (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The research aims to find out how the form of community participation in the tourism object of Pulau Pinus II, tourism development strategies, and the application of CBT by tourism development strategies. Researchers used descriptive methods and swot analysis using six respondents who were considered to have an important and influential role in the tourism object of Pulau Pinus II.The study results showed community participation in the form of guarding retribution tickets, ship transportation, cleaning, managing annual activities, and making souvenirs. The development strategy created is the S-O strategy; first, Creating new attractions or rides to optimize the potential of the natural beauty of tourism objects so that more tourists want to visit, not only during holidays. Second,by Promoting through social media or making banners to increase the potential of domestic or foreign tourists to visit and find out about tourism objects, the application of CBT can be done is to involve community participation in decision-making and empowering the community.